A MODEL OF HIGH–SPEED INTERACTION IN THE «STRIKING ELEMENT – BARRIER» SYSTEM - A.I. Godunov; P.S. Suzdaltsev; N.A. Kuzin (Надежность и качество сложных систем)
Background. In modern conditions, the development of mathematical models plays a key role in the research and design of technical systems. The creation of adequate models makes it possible to increase the accuracy of predicting the behavior of objects and optimize their characteristics. Materials and methods. The paper builds a mathematical model of the object under study using modern computational methods. Numerical calculation methods and software for modeling dynamic processes are used. Results. The developed model makes it possible to analyze the main parameters of the system, determine its dynamic characteristics and the influence of external factors on the behavior of the object under study. Conclusions. The proposed approach to mathematical modeling ensures high accuracy and reliability of the results, which can be useful in the development and improvement of technical systems.